The Role of Student Worksheet Media in Moderating Student Achievement - Marwah, Amelia Siti; Najmudin, Najmudin; Naufalin, Lina Rifda (Universitas Negeri Semarang, 2021)
The purpose of this research is to analyze the impact of student’s independence (learning by self motivation) and readiness (condition for ready to learn) moderated by student worksheets media on student’s achievement in examination score. The survey is a method used to analyze the purpose. Data collection techniques used in this research are documentation and survey/questionnaire used to learn the student’s responses on the independent learning, learning readiness, and Student Worksheets learning media. The population are 252 students at class eleventh and selected by probability sampling. The sampling technique in this research was using probability sampling by simple random sampling with the amount of sample are 155 students. The sample is calculated using the Slovin formula with an error rate 5%. The multiple regression with moderator variable is used to analyze the data. The finding of the research suggests that student’s independence and readiness in studying has partially a positive influence on student’s achievement; student worksheets media able to moderate the influence of both student’s independence and readiness in studying on on student’s achievement.